China's high-speed rail project as a debt trap? lessons learned from Sri Lanka's bankruptcy situation - Dewantara, Bachtiar; Pawar, Avinash; Ramdhany, Muhamad Arief; Fathulliansyah, Noor; Loupias, Henry H. (ARKA INSTITUTE, 2025)
Speed Rail (KCIC) project, developed under China’s Belt and Road Initiative (BRI). The research addresses the urgency of assessing whether large-scale infrastructure projects financed through bilateral loans risk creating long-term debt dependency, drawing lessons from Sri Lanka’s Hambantota Port case. The objectives are to evaluate the potential of the KCIC to drive economic growth while identifying financial vulnerabilities, and to explore how such insights can contribute to civic education and policy literacy in Indonesia. A qualitative descriptive case study approach is applied, using secondary data from government reports, academic literature, and credible media sources, framed within dependency theory and the debt-trap diplomacy discourse. Findings reveal that although the KCIC has potential benefits for connectivity and investment attraction, significant cost overruns and reliance on long-term foreign loans may expose Indonesia to fiscal risks similar to those experienced by Sri Lanka. Policy recommendations include diversifying financing sources, enhancing project governance, and embedding infrastructure analysis into public policy and strategic leadership education. These measures can strengthen national capacity to negotiate and manage large-scale infrastructure projects, aligning economic development with sustainable sovereignty.